Simulasi Pengontrol Fuzzy Logic Sudut Pitch Blade pada Turbin Angin Menggunakan Simulink MATLAB - Priyanto, Eko Dwy; ZA, Ahmad Azhar (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2022)
In places with limited wind resources, only the installation of Small Horizontal-Axis Wind Turbines (SHAWT) can be advantageous. With today's technological advances, wind turbines must have more sophisticated controls. The aim of this research is to simulate the blade pitch angle control in a wind turbine using fuzzy logic based on Matrix Laboratory (MATLAB). Then the blade pitch angle on the wind turbine can be controlled steadily. The wind speed input parameters are determined in advance so that the blade pitch angle parameter can be obtained, and the resulting mechanical power output parameters are in the 20,000 watt range. The study's findings include Simulink simulations in MATLAB and blade pitch angle plant on wind turbines that can achieve stable conditions. The fuzzy logic controller simulation in the blade pitch angle plant on the wind turbine has a high level of stability. However, the time needed to achieve stability is relatively long compared to other controllers. The conclusion of this research is that Simulink in MATLAB can simulate the process of controlling the balde pitch angle on a wind turbine with a fuzzy logic controller. Next, the blade pitch angle plant on a wind turbine with a fuzzy logic controller can be controlled stably at an input wind speed of 20 m/s with a rated power value between 18,000 and 20,000 Watts.